Influence Of Health Behaviour Factors On Basic Immunisation In Indonesia 2022 - Efri Diah Utami; Syifa Faikhatul Ilmi (Universitas Muhammadiyah Malang, 2024)
Background: The coverage of complete basic immunisation in Indonesia from 2020 to 2022 never reached the target of the 2020-2024 National Medium-Term Development Plan despite various efforts made by the government. As a result, there are many cases of infectious diseases in children. Therefore, this study aims to determine the overview of the coverage of complete basic immunisation in Indonesia in 2022 and the effect of antenatal care visits, doctor ratio, and ownership of immunisation documents on the coverage of complete basic immunisation in Indonesia in 2022. Methods: This study uses data from the Central Bureau of Statistics publication and the Ministry of Health publication. The analysis method used in this study is multiple linear regression analysis. Results: Antenatal care visits and the ratio of doctors have a positive and insignificant effect on the coverage of complete basic immunisation in Indonesia in 2022 while ownership of immunisation documents has a significant positive effect. Conclusion: The variable of ownership of immunisation documents is the most influential variable on the coverage of complete basic immunisation. This variable will increase the coverage of complete basic immunisation by 1.377 percent every 1 percent increase in the percentage of ownership of immunisation documents.